Two-dimensional modeling of nitrate transport in canola field under Moistube irrigation using HYDRUS 2D/3D - Tinashe Lindel Dirwai; Tinashe Lindel Dirwai; Aidan Senzanje; Aidan Senzanje; Tafadzwanashe Mabhaudhi; Tafadzwanashe Mabhaudhi; Tafadzwanashe Mabhaudhi; Tafadzwanashe Mabhaudhi (Frontiers in Sustainable Food Systems, 2025)
IntroductionUnderstanding nitrate distribution and leaching under various irrigation strategies is critical for optimizing nitrogen use efficiency and minimizing environmental losses. While previous studies have explored wetting patterns under Moistube Irrigation (MTI) and discussed qualitative nitrate retention, few have quantitatively simulated nitrate transport through variably saturated zones with fine temporal-spatial resolution.MethodsA field experiment was conducted in a 20 m × 8 m naturally ventilated greenhouse using three irrigation regimes: (i) full irrigation (100% ETc), (ii) optimal deficit irrigation (75% ETc), and (iii) extreme deficit irrigation (55% ETc). Each regime was replicated across four 2 m × 1 m plots, physically and hydrologically separated by 1 m buffers. Fertilizer was applied at 210 ppm in two split applications. Soil samples were collected both adjacent to and 15 cm away from MTI laterals at multiple depths before and at 2 h, 4 h, 24 h, 48 h, and 72 h post-fertigation. HYDRUS 2D/3D was used to simulate solute transport, while nitrogen use efficiency was evaluated using the partial factor productivity of applied nitrogen (PFPN).ResultsThe 55% ETc regime showed the highest nitrate leaching, followed by the 75% ETc regime. Full and optimal deficit irrigation regimes achieved yields ≥ 1.15 ton.ha−1 and PFPN values of 1.72 kg.kg−1 and 1.29 kg.kg−1, respectively. HYDRUS 2D/3D accurately simulated solute transport for full and optimal DI regimes with performance metrics [nRMSE ≤ 0.24, EF ≤ 0.54, PBIAS ≤ −7.41%], but performed poorly under the extreme deficit irrigation.DiscussionThe findings suggest that optimal deficit irrigation under MTI enables effective fertigation with minimal yield penalties, offering a balance between water savings and nutrient retention. MTI, combined with precise fertigation scheduling, shows promise as a climate-smart agriculture solution, particularly in nitrate-sensitive zones. The study confirms the feasibility of using MTI beyond laboratory settings, with implications for sustainable intensification in semi-arid regions.